Vitamin E and MDA Concentrations in Plasma of Healthy Young Adult, Elderly and Pregnancy - Sri Rahajoe Asj'ari; Prasetyastuti Prasetyastuti; Zainal Arifin N.A.; Ngadikun Ngadikun; Aalda Ellen Manampiring; Risanto Siswo Sudarmo; Sulchan Sofoewan (Indonesian Food and Nutrition Progress, 2003)
Vitamin E is one of essential micronutrients. It is an antioxidant which potentially protects bioinolecules against oxidative damage. One ofparameters ofoxidafive damage is MDA or lipid peroxide. In this study, concentrations of plasma vitamin E as an antioxidant and MDA as one of oxidative damage markers were measured. The subjects consisted offive groups: (I) male medical students (young adult), (II) female medical students (young adult), (III) nursery inhabitants in Yogyakarta province (Abiyoso), (IV) nursery inhabitants in Manado, North Sulawesi Province (Senja Cerah), as the old ages, and (V) pregnant women within third trimester (of Prenatal Care Unit in Sardjito Hospital). The concentrations of Vitamin E (mg/dl) and MDA (nmol/ml) were as follows: Young Adult Male (n= 28) 20,8 + 3,8 and 0,190 + 0,057 ; Young adult Female (n-28) 21,9 + 4,5 and 0,123 + 0,057 ; Old age Yogyakarta (n=41) 30,6 + 10,4 and 0,291 + 0,062 ; Old age Manado (n=40) 26,5 + 4,5 and 0,391 + 0,081 ; Pregnant Women (=28) 39,9 + 11,3 and 0,165 -f 0,067. Groups of people who were hyperlipemic tend to have high concentration of Vitamin E, while group IV who eat less vegetable protein and more PUFA tend to have higher MDA concentration.